Investigation on impact resistance of hierarchical lightweight lattice structure. Issue 1 (1st April 2022) - Gan, Jiakang; Ji, E; Li, Bing
Abstract: This paper is majorly discussing the impact resistance of hierarchical lightweight lattice structure. Firstly, the unit cells of hierarchical pyramidal lattice structure and traditional single-stage hollow pyramidal lattice structure are designed. At the same time, the concept of relative density is introduced to better demonstrate the impact resistance of hierarchical structure. In this paper, ABAQUS/Explicit software is used to simulate the drop hammer impact simulation of hierarchical structure and hollow structure. The result shows that the impact resistance of hierarchical structure is better than hollow structure. Meanwhile, the samples are prepared by 3D printing, and then quasi-static compression experiment and drop hammer impact experiment are carried out. It is concluded that the bearing and impact resistance performance of the hierarchical structure has obvious improvement than the hollow structure under both quasi-static compression and low-speed drop hammer impact.